2018
DOI: 10.1007/s11099-017-0737-9
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced changes in photosynthetic parameters and peroxidase isoenzyme contents in tomato (Solanum lycopersicum L.) plants

Abstract: Tomato samples were collected from the field of Absheron peninsula in Azerbaijan in order to evaluate the incidence of main Tobamoviruses. According to results of serological and molecular tests, Tomato mosaic virus (ToMV), Tobacco mosaic virus (TMV), and Pepper mild mottle virus (PMMoV) were detected as single and mixed infections (TMV + PMMoV; ToMV + PMMoV) in various tomato samples. It was found that Tobamovirus infection caused an increase in the content of malondialdehyde, alterations in the activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Chlorophyll content was an important indicator of leaf photosynthetic ability, which was closely related to the host disease resistance, when the host plant was infected by the virus, chlorophyll decomposition enzyme was activated, resulting in a decrease in chlorophyll content, thereby affecting leaf photosynthesis and reducing the host disease resistanced [30][31] . The results showed that the chlorophyll content in N. benthamiana infected with AMV and WCMV reached a maximum of 0.98 mg/g at the 6th day after inoculation, which was reduced by 17.34%, 31.63% and 50.00% compared with AMV, WCMV alone and healthy baccobacterium N. benthamiana (CK), respectively, This was consistent with the results [32] and other studies that found that citrus yellow vein clearing virus (CYVCV) can lead to a decrease in chlorophyll content in sweet oranges; through electron microscopy, two forms of viruses were observed in the juice of bacillus N. benthamiana disease infected by AMV and WCMV, and spheroidal and linear viruses were also found in the juice of AMV and WCMV infected with baccobacterium bency, respectively, with lengths between 20~75 nm and 400~600 nm, respectively, and the results of this study and AMV viruses were bacterium-like or quasi-equiaxial elongated, with a size of 18~20 nm× At 58~18 nm, WCMV viruses are curved and linear [33] , with sizes of 480 ×13nm × similar results, but the performance of viruses in the host was often more complex, and the viruses of the same genus are similar in morphology, and the speci c virus cannot be accurately observed only by electron microscopy, so further research was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll content was an important indicator of leaf photosynthetic ability, which was closely related to the host disease resistance, when the host plant was infected by the virus, chlorophyll decomposition enzyme was activated, resulting in a decrease in chlorophyll content, thereby affecting leaf photosynthesis and reducing the host disease resistanced [30][31] . The results showed that the chlorophyll content in N. benthamiana infected with AMV and WCMV reached a maximum of 0.98 mg/g at the 6th day after inoculation, which was reduced by 17.34%, 31.63% and 50.00% compared with AMV, WCMV alone and healthy baccobacterium N. benthamiana (CK), respectively, This was consistent with the results [32] and other studies that found that citrus yellow vein clearing virus (CYVCV) can lead to a decrease in chlorophyll content in sweet oranges; through electron microscopy, two forms of viruses were observed in the juice of bacillus N. benthamiana disease infected by AMV and WCMV, and spheroidal and linear viruses were also found in the juice of AMV and WCMV infected with baccobacterium bency, respectively, with lengths between 20~75 nm and 400~600 nm, respectively, and the results of this study and AMV viruses were bacterium-like or quasi-equiaxial elongated, with a size of 18~20 nm× At 58~18 nm, WCMV viruses are curved and linear [33] , with sizes of 480 ×13nm × similar results, but the performance of viruses in the host was often more complex, and the viruses of the same genus are similar in morphology, and the speci c virus cannot be accurately observed only by electron microscopy, so further research was needed.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is a final product of fatty acid peroxidation caused by ROS accumulation [48]. MDA is used as an indicator for lipid peroxidation and oxidative stress due to the overproduction of ROS because of virus infection [49,50]. In the present, CGMMV infection caused the accumulation of MdA, indicating lipid peroxidation and oxidative stress.…”
Section: Treatmentsmentioning
confidence: 99%
“…The skeleton of E 3 consisted of a pyrazole ring and a 1,3,4-thiadiazole ring, which were connected by C (9) and C (10). The benzene ring and NH 2 group were connected to the pyrazole ring at the 1-position and 5-position by N (13)-C (4) and N (5)-C (12), respectively. The benzyl group was connected with the 1,3,4-thiadizole ring by C (8)-S (1)-C (7).…”
Section: Chemistrymentioning
confidence: 99%
“…Nevertheless, photosynthetic activity is determined by the chlorophyll content, which also reflects the health of plants and has an important impact on plant growth [8][9][10]. The chlorophyll content and the net photosynthesis (Pn) decrease in the leaves of infected plants [11,12].…”
Section: Introductionmentioning
confidence: 99%